2018
DOI: 10.5511/plantbiotechnology.18.0510b
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional enhancement of a bacterial <i>choline oxidase A</i> gene by an <i>HSP</i> terminator improves the glycine betaine production and salinity stress tolerance of <i>Eucalyptus camaldulensis</i> trees

Abstract: Novel transgenic Eucalyptus camaldulensis trees expressing the bacterial choline oxidase A (codA) gene by the Cauliflower mosaic virus (CaMV) 35S promoter and the Arabidopsis thaliana heat shock protein (HSP) terminator was developed. To evaluate the codA transcription level and the metabolic products and abiotic stress tolerance of the transgenic trees, a six-month semi-confined screen house cultivation trial was conducted under a moderate-stringency salt-stress condition. The transcription level of the CaMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The genetic backgrounds of the transgenic E. camaldulensis generated by the method used in this study were heterozygotic, because hypocotyls of the seedlings derived from the bulk seeds were used as the explants in the transformation experiments. We also observed similar morphological characteristics in the transgenic E. camaldulensis harbouring another transgene but generated around the same time (Tran et al ., ). From these facts, we considered that the morphological characteristics of 2‐5‐4 and 2‐5‐7 were not caused by McRBP expression but rather by polymorphism within the bulk seeds.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The genetic backgrounds of the transgenic E. camaldulensis generated by the method used in this study were heterozygotic, because hypocotyls of the seedlings derived from the bulk seeds were used as the explants in the transformation experiments. We also observed similar morphological characteristics in the transgenic E. camaldulensis harbouring another transgene but generated around the same time (Tran et al ., ). From these facts, we considered that the morphological characteristics of 2‐5‐4 and 2‐5‐7 were not caused by McRBP expression but rather by polymorphism within the bulk seeds.…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that a transgenic E. camaldulensis harbouring a codA gene—which was derived from the soil bacterium Arthrobacter globiformis (Ikuta et al ., ) and encodes an enzyme related to the synthesis of glycine betaine, an osmoprotectant (Ashraf and Foolad, ; Chen and Murata, ; Giri, ; Kurepin et al ., )—also survived and showed a significant reduction of growth decline due to salt stress compared with the non‐transgenic E. camaldulensis lines (Tran et al ., ). Relative growth under 6‐month salt treatment was higher in the McRBP transgenic lines than the codA transgenic lines—i.e., the relative growths of the McRBP , codA , and non‐transgenic lines were in the ranges of 8.0–10.0, 6.8–7.7, and 4.6–6.0, respectively (Figure c; Tran et al ., ). These results would suggest that McRBP is superior to codA as a transgene conferring chronic moderate stress‐tolerance to E. camaldulensis , but other factors, such as the transcriptional levels and the insertion positions of their transgenes, should also be considered.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations